(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
"Atuado" is the term used in Pajelança Cabocla de Pena and Maracá to refer to the body in pajé performance. This article brought the proposition of an approximation of this practice and some reflections on the possible dialogues of the notion of actuated with the contemporaneity of performing and performing arts. To this end, it was hypothesized that this crossing offers elements with fertility value for a scene that rehearses new ways of thinking and seeing the worlds. The proposition came from the meeting of the author of this article with the memory of her grandmother, a pajé cabocla de pena and maracá, and imbriced fieldwork in the Marajó with questions of the Arts of Scene and thoughts that discuss and unfold the concept of Amerindian perspective.